2015
DOI: 10.1002/gps.4264
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning throughout the treatment history of clinical late‐life depression

Abstract: Objective Previous investigations into the relationship between late-life depressive symptoms and cognitive functioning have resulted in mixed findings concerning whether or not depressive symptoms and cognitive functioning are related. The mixed reports may be due in part to differences in clinical and nonclinical samples and to inadequate consideration of the dynamic nature (i.e., fluctuating course) of depressive symptoms and cognitive functioning in older adults. The current study examined the chronic, acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…An important finding of this study is that even rather modest intraindividual change in depression exerts significant influence on cognitive performance in the general population. Thus, our results extend the findings from a previous study targeting a population of depressed individuals (Dzierzewski et al 2015 ). The observed effects may reflect changes due to environmental factors, or feeling more happy or sad on a particular day.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An important finding of this study is that even rather modest intraindividual change in depression exerts significant influence on cognitive performance in the general population. Thus, our results extend the findings from a previous study targeting a population of depressed individuals (Dzierzewski et al 2015 ). The observed effects may reflect changes due to environmental factors, or feeling more happy or sad on a particular day.…”
Section: Discussionsupporting
confidence: 91%
“…The results have implications for the interpretation of cognitive test scores, as using scores based on only one occasion may give a somewhat misleading picture of that individual's actual cognitive abilities. The fluctuating nature of depression and its impact on cognitive performance may explain some of the inconsistencies in previous research concerning depressive symptoms and cognitive decline (Han et al 2006 ; Dzierzewski et al 2015 ). From a treatment perspective, the results from this study also show that when levels of depression go down, cognitive performance improves.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A prospective study involving LOD patients ( n = 453) found increasing age, lower education status, and chronicity of depression as risk factors for poor cognitive performance. 27 Similarly, another prospective study noted a positive effect of education and a negative effect of cerebral comorbidity (stroke and Parkinson’s disease) on cognitive performance in LOD. 28 A systematic review of eight studies, which does not include previously mentioned studies, investigated the association between executive dysfunction and severity of depression in older adults.…”
Section: Cognitive Deficits In Lodmentioning
confidence: 94%
“…Ευρήματα άλλων ερευνητών επιβεβαιώνουν ότι η χαμηλή ή μέτρια αυτοαναφερόμενη υγεία συνδέεται με μεγαλύτερα odds εμφάνισης χρόνιων ασθενειών και καταθλιπτικών συμπτωμάτων (Ambresin et al, 2014;Kim, 2.8 Ανάλυση των δεδομένων κατά φύλο 48 2010). Αντίστοιχα, σε υγιή άτομα μεγάλης ηλικίας, αν παρουσιαστούν γνωστικές δυσλειτουργίες μπορούν να οδηγήσουν σε καταθλιπτικά συμπτώματα και ακόμα και σε άνοια στην περίπτωση που δεν αντιμετωπιστούν επιτυχώς μετά από κατάλληλη αγωγή (Dzierzewski et al, 2015;Wilkins et al, 2009). Η οικονομική εξασφάλιση των νοικοκυριών δίνει έναν αντισταθμιστικό παράγοντα καλύτερης ψυχικής υγείας και ευημερίας στην όψιμη ενήλικη ζωή.…”
Section: περιγραφική ανάλυση των μεταβλητών ενδιαφέροντοςunclassified